Enhancing professionalism in post-graduate medical education: the initial implementation and evaluation of a longitudinal curriculum for geriatrics residents in Toronto, Canada - Kristina M Kokorelias; Muhammad Harris Sheikh; Maryam Naimi; Bernice Ho; Edwin W Wong; Stephanie G Brooks; Dov Gandell; Arielle S Berger (Canadian Medical Education Journal)
Background: Professionalism is vital in medicine, yet gaps exist in its teaching within post-graduate medical education (PGME).